Circular RNA as a Potential Biomarker for Melanoma: A Systematic Review - Tang, Keyun; Zhang, Hanlin; Li, Yaqi; Sun, Qiuning; Jin, Hongzhong (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are newly discovered RNAs with covalently looped structures. Due to their resistance to RNAase degradation and tissue-specific expression, circRNAs are expected to be potential biomarkers in early diagnosis and target treatment of many diseases. However, the role of circRNAs in melanoma still needs to be systematically reviewed for better understanding and further research. Based on published articles in PubMed, Embase, Cochrane Library, and Web of Science database, we systematically reviewed the implications and recent advances of circRNAs in melanoma, focusing on function, mechanism, and correlation with melanoma progression. According to inclusion and exclusion criteria, a total of 19 articles were finally included in this systematic review. Of the 19 studies, 17 used human samples, including melanoma tissues (n = 16) and blood serum of patients with melanoma (n = 1). The sample size of the study group ranged from 20 to 105 based on the reported data. Several studies explored the association between circRNAs and clinicopathological characteristics. circRNA dysregulation was commonly observed in melanoma patients. circRNAs function in melanoma by miRNA sponging and interaction with RNA binding proteins (RBP), ultimately controlling several important signaling pathways and cancer-related cellular processes, including proliferation, migration, invasion, metastasis, apoptosis, and glucose metabolism. circRNA expression could be associated with prognostic factors and drug responses, consolidating the potential clinical value in melanoma. Herein, we clarified the functional, prognostic, and predictive roles of circRNAs in melanoma in this systematic review, providing future directions for studies on melanoma-associated circRNAs.